ANALISIS KONFLIK ANTARA KEPALA DAERAH DENGAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DKI DALAM PENETAPAN ANGGARAN PENDAPATAN BELANJA DAERAH (APBD) TAHUN 2015 - Azilla, Syarifah Nirda; ., Turtiantoro; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2016)
ANALYSISAbstractThe Analysis of conflict between regional head and Regional People'sRepresentatives Assembly (DPRD) in determining regional government budget(APBD) 2015 shows of relationship between Regional Head and RegionalPeople's Representatives Assembly in terms of regional government functions.Implementation of regional government functions will perform optimally ifimplementation of government affairs are followed by sufficient distribution ofrevenue sources to regional head. All financial resources related to any regionalgovernment matters are recognized as regional finance. Management of regionalfinance itself can’t be separated from budget that is better known as regionalgovernment budget (APBD). Regional government budget is an instrument thatwill ensure the creation of decision making process. Regional government budgetis one of the Regional People's Representatives Assembly (DPRD) decisionmaking duties. Regional government budget is a regional annual plan that arediscussed and agreed upon by regional government and Regional People'sRepresentatives Assembly (DPRD) and set by local regulations.Regional Government Budget (APBD) is prepared and implemented bylocal governments . All the activities carried out by local governments are basedon the development design and allocations which require the approval of DPRD.Regional People's Representatives Assembly (DPRD) function includesestablishing regulations, budgeting and oversights. One is to supervise theimplementation of the Regional Budget (APBD) to avoid any deviation. Thiscould be viewed as accountability instrument for regents, governor or mayor inregards to DPRD. However, in practice it is not uncommon to be a potentialsource of conflict between Regent, Governor, or Mayor and DPRD.Keywords: Conflict, Regional Government, Regional Head, DPRD, RegionalFinance, APBD